Lectio Praecursoria: Aspired Communities—The communities of long-term recovery after the 3.11 disaster in the town of Yamamoto - Pilvi Posio (Suomen Antropologi, 2023)
I argue in this thesis that we can understand the various ways in which community is ontologized as a tangible, affective and compelling social reality through the analytical lens of the future orientation of collective aspiring. The social and material lives of the residents in the disaster-stricken Tohoku region of northeast Japan were drastically altered after the Great East Japan Earthquake and the tsunami on March 11 in 2011. Based on eight months of ethnographic fieldwork in 2014–2015 in the town of Yamamoto, I seek to understand in this PhD thesis how the local communities were recovering during the still-ongoing reconstruction then. The main objective of this thesis is to offer analytical tools to explore how people come to interpret, experience and feel their social existence as community.